Strategic Management Mechanisms for Real Estate Agencies ("Journal "U". Economy. Management. Finance.", 2021)
The article discusses the concept of a strategic management mechanism and defines their types. As part of the study, the essence of each of the proposed mechanisms was considered and the possibility of their application in real estate agencies was analyzed.
Keywords: strategy; strategic management; strategic management mechanism; real estate agency